PARENTAL PERCEPTIONS OF RELIGIOUS MODERATION EDUCATION FOR GENERATION ALPHA THROUGH ANIMATED FILMS - Putra, Eka Mahendra (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Purpose: This study aims to analyze parents’ perceptions of instilling religious moderation values in Generation Alpha through animated films, particularly Nussa & Rara and Riri Cerita Anak Interaktif, focusing on parents of tenth-grade students at SMA Muhammadiyah 6 Makassar. Method: Using a qualitative-descriptive approach, this research explores parents’ experiences, views, and practices in guiding their children's media consumption in the digital era. Result: The findings indicate that both animated films are perceived as effective media for conveying key values of religious moderation, such as tolerance, appreciation of diversity, peaceful conflict resolution, and balanced religious understanding. However, the effectiveness of these values’ internalization is strongly influenced by parental accompaniment, which serves as a mediator between the film’s messages and the child’s real-life context. Challenges identified include exposure to diverse digital content, limited parental supervision time, and variations in parents’ understanding of religious moderation. Conclusion: This study highlights that synergy between educational animated media, family media literacy, and formal education is essential to strengthen the internalization of religious moderation values in Generation Alpha.